KARAKTERISTIK DAN AKTIVITAS WISATAWAN MANCANEGARA PASCA ERUPSI DI KABUPATEN KARANGASEM - NGAS. Dewi (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
Mount Agung, which is the highest active mountain in Bali, began to experience an eruption which immediately caused Bali tourism to collapse. On the other hand, this disaster invites a special attraction for special interest tourists. This paper aims to determine the characteristics and activities of foreign tourists after the eruption of Mount Agung in Karangasem Regency. Data collection techniques used, among others: observation, interview, questionnaires distributions, literature study, and documentation with qualitative descriptive and quantitative analysis methods. Based on the results of data analysis, it is known the characteristics of foreign tourists based on tourist descriptors, namely: age dominated by 20 - 35 years (81%), coming from France (18%), female sex (57%), unmarried status (60%), recent undergraduate education (52%), employment of private employees (38%), income> USD 510 (57%). Meanwhile, characteristics based on trip descriptor have results that are dominated by: Bali as the main destination (88%), first visit to Bali (71%), length of stay in Bali more than 5 days (80%), visit with friends (36% ), stay at homestay (33%), accommodation located in Ubud (31%), length of stay in Karangasem <1 day (52%), organize trips independently (74%), expenses in Karangasem <1,000,000 (72%) ), car and driver rental (41%). Tourism activities undertaken by foreign tourists after the eruption of Mount Agung were dominated by cultural tourism activities with the highest Likert scale of 3.37 in the category of strongly agree.